Sex differences in the determination of prescribed load in ballistic bench press - Izadi, Mohammad; Pillitteri, Guglielmo; Thomas, Ewan; Battaglia, Giuseppe; Bianco, Antonino; Bellafiore, Marianna (Frontiers in Physiology, 2024)
The objectives of the present study were twofold: first, to identify the specific relative load at which the concentric motion transforms into a purely propulsive action among women, and second, to compare the load-velocity relationships between men and women during the bench press throw. Fourteen men and fourteen women participated in a test where they progressively increased the load until reaching their onerepetition maximum (1RM) in the bench press exercise. Linear regression models were employed to elucidate the relationships between load and velocity, as well as load and the propulsive phase (% of total concentric time). Additionally, ANCOVA was utilized to compare the linear regression models between men and women. The results revealed strong and linear associations between load and mean propulsive velocity (MPV) for both men and women, as well as between load and the propulsive phase. Notably, there were significant differences in MPV and the propulsive phase concerning load between men and women.Women transitioned into a fully propulsive concentric phase at approximately 80% of their 1RM, while men achieved this entirely propulsive phase at around 85% of their 1RM. Furthermore, women exhibited reduced velocities when handling lighter relative loads compared to men. Conversely, women demonstrated higher velocities when dealing with loads exceeding 85% of their 1RM in contrast to their male counterparts. These findings have significant implications for tailoring recommended bench press throw loads for women, which should be distinct from those suggested for men.